Application of the 980-nm diode laser in stereotaxic surgery - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1999)
With recent developments in laser technology, diode laser and optical delivery systems have become highly promising surgical devices with advantages of lower cost and higher precision, The aim of the present study was to test the 980-nm diode laser for its potential use in stereotaxic surgery. In our dosimetric study, the response of cortical tissue to different energy levels of laser irradiation was investigated with different exposure durations. In vivo stereotaxic neurosurgical procedure was performed on female Wistar rats weighing 180 to 220 gr, In order to investigate the lesioning effects of the 980-nm diode laser as a function of pulse duration, laser power was adjusted to 2.0 and 3.0 W with exposure times ranging from 1.3 to 3.0 s resulting in an irradiance of 5.97 to 17.91 J/mm(2). Histologic investigation of brain specimens indicated that the 980-nm diode laser has the potential to create lesions in stereotaxic surgery. With proper selection of power level and exposure duration, target tissues could be evaporated and/or coagulated. We found the 980-nm diode laser a promising tool for neurosurgical applications.
Keywords: 980-nm diode laser; coagulation; cortex; laser-tissue interactions; stereotaxic neurosurgery; NEUROSURGERY; ABLATION; DAMAGE; TISSUE; BRAIN; YAG